2015
DOI: 10.1038/nphys3503
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a d-wave gap in electron-doped Sr2IrO4

Abstract: High-temperature superconductivity in cuprates emerges out of a highly enigmatic 'pseudogap' metal phase. The mechanism of high-temperature superconductivity is probably encrypted in the elusive relationship between the two phases, which spectroscopically is manifested as Fermi arcs-disconnected segments of zero-energy states-collapsing into d-wave point nodes upon entering the superconducting phase. Here, we reproduce this distinct cuprate phenomenology in the 5d transition-metal oxide Sr 2 IrO 4 . Using angl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
265
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(282 citation statements)
references
References 36 publications
17
265
0
Order By: Relevance
“…The formation of a half-filled t 2g doublet by the strong Ir spin-orbit interaction, that is then gapped by correlations, mimics what is seen in the cuprates, making Sr 2 IrO 4 an insulator, despite its Ir 4+ ionic configuration with five occupied t 2g electrons [1,2]. More recent experiments on doped iridates point to the emergence of a pseudogap [3] and at low temperatures a d-wave gap [4], therefore strengthening the analogy with cuprates. Most recently, a new experiment based on second-harmonic generation (SHG) [5] claimed the detection of an oddparity, magnetic hidden order in Sr 2 IrO 4 , suggesting the presence of orbital currents as proposed by Varma for cuprates [6].…”
Section: Introductionmentioning
confidence: 76%
“…The formation of a half-filled t 2g doublet by the strong Ir spin-orbit interaction, that is then gapped by correlations, mimics what is seen in the cuprates, making Sr 2 IrO 4 an insulator, despite its Ir 4+ ionic configuration with five occupied t 2g electrons [1,2]. More recent experiments on doped iridates point to the emergence of a pseudogap [3] and at low temperatures a d-wave gap [4], therefore strengthening the analogy with cuprates. Most recently, a new experiment based on second-harmonic generation (SHG) [5] claimed the detection of an oddparity, magnetic hidden order in Sr 2 IrO 4 , suggesting the presence of orbital currents as proposed by Varma for cuprates [6].…”
Section: Introductionmentioning
confidence: 76%
“…La-doped Sr 2 IrO 4 single crystals have only become available in the last couple of years [21][22][23] , but angle-resolved photoemission studies on them 21,22 do not fully reproduce the observations made via the in situ doping method 12,16 . While it is unclear at the moment what leads to such differences between the two doping methods, we note that a well-defined quasiparticle peak is absent for any doping level in La-doped samples, indicating suppressed coherent motion of doped electrons presumably due to disorder created by chemical doping.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, tantalizing indications of d-wave superconductivity have been seen in electron-doped Sr 2 IrO 4 16,17 : a gap of predominantly d-wave symmetry is observed in the low-temperature angle-resolved photoemission spectra 16 , and a particle-hole symmetric density of states is observed in scanning tunneling spectra below a temperature as high as 50 K 17 . Above this temperature, the d-wave gap evolves into a pseudogap, in striking parallel with the cuprates 12,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, 3 Recently in situ surface electron doping by potassium deposition has been achieved, and it was found that Fermi arcs, pseudogap, and a low-temperature d-wave gap exist for these samples demonstrating properties in complete analogy with the cuprates. [5][6][7] These studies on Sr 2 IrO 4 suggest that properties of other iridates might also be highly tunable. Recently the layered honeycomb lattice Iridates A 2 IrO 3 (A = Na, Li) have been recognized as spin-orbit assisted J eff = 1/2 Mott insulators.…”
Section: Introductionmentioning
confidence: 99%